The Relationship between Safety Management Practices with Worker Safety Compliance Behaviour in Manufacturing Sector - Sivanantha, Madewan (2020)
Safety management practices are essential to reduce hazardous incidents at the workplace by improving safety conditions at the workplace, as well as encouraging employers and employees to shift their attitudes and behaviors in order to place an importance on safety and health. The purpose of this study is to review the level of safety compliance among the workers in manufacturing company and to review the relationship between safety compliance as dependent variable with the independent variables which are safety management practices which look at management commitment, safety training, and the involvement of the workers, safety communication, promotion of safety and safety rules & procedures. The research method is quantitative analysis and adopting a cross-sectional approach in data gathering. Primary data generated form the questionnaire chose as a data collection. Random sampling method was used in collecting the data and the population is from the Fabricated Metal and Hardware manufacturing company in Nibong Tebal, Pulau Pinang. Quantitative analysis using SPSS version 25.0 was used and the result is showed that the six factors of safety management practices affect the safety behaviors (safety compliance). The findings from this study will provide useful insight for future researchers and practitioners in the field to identify issues and solutions that contribute to safety and health at the workplace.